TINJAUN YURIDIS PENERAPAN DELIK PERCOBAAN PADA PUTUSAN NOMOR 200/PID.B/2018/PENGADILAN GUNUNG SITOLI - Reynaldi Santoso; Amar Taufiq; Sandro Oktora Tampubolon; Bintang Fahraji; Rizki Rizki (UNES Law Review, 2021)
Attempted murder is one of the crimes. Attempted murder has been regulated in Article 338 in conjunction with Article 53 of the Criminal Code. The formulation of the problem raised is how to apply a criminal offense in the case of attempted murder, and how the judge's consideration in the decision Number : 200/serious crime/2018/District Court/Gunungsitoli, the type of research used in this study is normative juridical with the use of a qualitative approach, data collection techniques in this study use document studies by analyzing secondary data sources and drawing conclusions deductively, begin van uitvoering is explained as the beginning of the implementation in an attempt to commit a criminal offense, which is where the act can be interpreted as an act of execution, when someone commits one of the elements of a criminal offense, and if the person has not committed one of these elements, then the action can be said to be just a preparatory act, judge’s consideration in decision number 200/Pid.b/2018/PN.Gst. that impose punishment on the perpetrator based on article 338 in conjuction with Article 53 Paragraph (1) The Criminal Code on attempted murder which the judge has corrected sentenced him to 5 years in prison.